1980
DOI: 10.1073/pnas.77.9.5480
|View full text |Cite
|
Sign up to set email alerts
|

Albumin Naskapi variant in North American Indians and Eti Turks.

Abstract: Both conventional polyacrylamide gel electrophoresis and a new type of electrophoretic screening procedure indicate that the polymorphic albumin variants Naskapi, found chiefly in the Naskapi Indians of Quebec, and Mersin, found in the Eti Turks of southeastern Turkey, are molecularly identical or very similar and that the amino acid substitution site in these variants is located between residues 330 and 446. This discovery is consistent with a genetic relationship between the Eti Turks and American Indians. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
11
0

Year Published

1987
1987
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…We had received the last remaining sample of the Adana serum (<1 ml) from B. Blumberg (Philadelphia) prior to receipt of the Vancouver and Birmingham specimens. In previous work (15,16) we had confirmed the report of Franklin et al (14) that CB6 was the site of substitution in this alloalbumin, but we had not identified the amino acid exchange. In our earlier study the total albumin from the Adana serum was purified and alkylated and was divided into two aliquots.…”
Section: Methodssupporting
confidence: 74%
See 2 more Smart Citations
“…We had received the last remaining sample of the Adana serum (<1 ml) from B. Blumberg (Philadelphia) prior to receipt of the Vancouver and Birmingham specimens. In previous work (15,16) we had confirmed the report of Franklin et al (14) that CB6 was the site of substitution in this alloalbumin, but we had not identified the amino acid exchange. In our earlier study the total albumin from the Adana serum was purified and alkylated and was divided into two aliquots.…”
Section: Methodssupporting
confidence: 74%
“…However, investigation of human albumin variants has 'recently been stimulated by the advent of improved methods for structural study of proteins, by interest in protein genetics and 'evolution, and by knowledge ofthe complete protein (8) and genomic (9) sequence ofalbumin. As summarized by Takahashi et al (10) (14,15).…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Here we report analytical studies of albumins Naskapi, Mersin, Adana, and Mexico-2, for which several genetic and epidemiological studies have been published (7,8,14,19).…”
mentioning
confidence: 99%
“…Albumin Adana is a variant identified in a single Eti Turk patient of the Adana district (19). The Adana variant is a slow migrating albumin, similar to albumin B as if it had a change of an acidic to a basic amino acid; however, the CNBr fragment pattern of Adana and B differ in our isoelectric focusing system and also in the PAGE system of Franklin et al (14,19). We have localized the substitution site of albumin Adana to CB6 (residues 447-548) ( Fig.…”
mentioning
confidence: 99%